Tresčí války: Island jako (ne)předpokládaný vítěz - Karkoš, Daniel (Univerzita Karlova, Fakulta sociálních věd, 2018)
This bachelor thesis deals with the Cod wars, a series of disputes between the United Kingdom and Iceland. The disputes were triggered by Iceland's unilateral extention of its territorial waters. It was caused by Iceland's fear of foreign fishermen's negative impact on local economy and culture. The disputes are unique, for the warring parties were partners within NATO. The disputes are nevertheless mostly interesting for the fact that their end was rather unexpected. Every time victory was on Iceland's side. This thesis investigates, what the reasons for such an outcome were. The investigation is done by an analysis of Icelandic national interests, devided into three categories with help of relevant theories of international relations. The outcome of this analysis is an identification of Icelandic advantages. Tato bakalářská práce se zabývá tresčími válkami, řadou sporů mezi Spojeným královstvím a Islandem. Spory byly podníceny islandským unilaterálním rozšiřováním teritoriálních vod. To bylo způsobeno obavou Islandu z negativního vlivu zahraničních rybářů na místní ekonomiku a kulturu. Specifičnost sporů tkví v tom, že strany sporů byly partnery v rámci Severoatlantické aliance. Zajímavé jsou však především proto, že jejich výsledek byl na první pohled nečekaný, vítězství bylo totiž vždy na straně Islandu. Tato bakalářská práce zjišťuje, co způsobilo tento výsledek, a to skrze analýzu islandských národních zájmů, rozdělených za pomoci relevantních teorií mezinárodních vztahů na tři kategorie. Výsledkem analýzy je identifikace výhod islandské strany. Department of European Studies Katedra evropských studií Fakulta sociálních věd Faculty of Social Sciences